ELECTROCHEMICAL ANALYSIS OF ZINECARD IN PHARMACEUTICAL AND BIOLOGICAL SAMPLES - Chennupalle Nageswara Reddy; Puthalapattu Reddy Prasad; Neelam Yugandhar Sreedhar (Faculty of Pharmacy Universitas Gadjah Mada, Yogyakarta, Skip Utara, 55281, Indonesia, 2012)
Zinecard is used to prevent a toxic effect to heart caused by certain medicines that are used to treat cancer. Zinecard is also used to treat tissue damage caused by the leakage of certain medicines that are used to treat cancer. Differential pulse polarographic method developed for the quantitative determination of zinecard gives a peak at -0.32 V at DME. From the structural point of view zinecard contains a >C=Omoiety which can be electrochemically reduced at universal buffer (pH 4.0). Millicoulometric experiment is performed successfully in estimating the number of electrons and proton to understand reduction mechanism. The differential pulse polarographic peak was adequately well-resolved, reproducible and linear dependent with the zinecard concentration. For quantification the calibration plot for zinecard concentrations ranging between 1.0×10-5mol dm-3 to 1.0×10-8mol dm-3 at pH 4.0 was selected. The proposed differential pulse polarographic method was successfully applied to the determination of zinecard in pharmaceutical formulations and urine samples.Key words: Zinecard, DPP, pharmaceutical formulations and urine samples.